The Development and Testing of a New Version of the Cognitive Reflection Test Applying Item Response Theory (IRT) - Primi, Caterina; Morsanyi, Kinga; Chiesi, Francesca; Donati, Maria Anna; Hamilton, Jayne (Journal of behavioral decision making, 2016)
The cognitive reflection test (CRT) is a short measure of a person's ability to resist intuitive response tendencies and to produce a normatively correct response, which is based on effortful reasoning. Although the CRT is a very popular measure, its psychometric properties have not been extensively investigated. A major limitation of the CRT is the difficulty of the items, which can lead to floor effects in populations other than highly educated adults. The present study aimed at investigating the psychometric properties of the CRT applying item response theory analyses (a two‐parameter logistic model) and at developing a new version of the scale (the CRT‐long), which is appropriate for participants with both lower and higher levels of cognitive reflection. The results demonstrated the good psychometric properties of the original, as well as the new scale. The validity of the new scale was also assessed by measuring correlations with various indicators of intelligence, numeracy, reasoning and decision‐making skills, and thinking dispositions. Moreover, we present evidence for the suitability of the new scale to be used with developmental samples. Finally, by comparing the performance of adolescents and young adults on the CRT and CRT‐long, we report the first investigation into the development of cognitive reflection. Copyright © 2015 John Wiley & Sons, Ltd.